Determining Premium for Disaster Reinsurance Program through Supply Chain Risk Management: An Application of Peak Over Threshold (POT) Approach - Sukono, Sukono; Subartini, Betty; Napitupulu, Herlina; Novitasari, Ela; Santoso, Agus; Ghazali, Puspa Liza; Saputra, Jumadil (ExcelingTech, 2020)
The purpose of this study is to determine the pricing (premium) for disaster reinsurance program. For those, this study uses the Peak Over Threshold (POT) approach, where the method pays attention to the pattern of heavy tail behaviour on the number of victims killed due to disaster events through extreme values with a reference value called the threshold u. The results of the analysis showed that the reinsurance premiums for flood disaster per year that must be paid by insurance company is IDR 712,008,900.50 with the maximum amount of reinsurance risk, L is IDR20,000,000,000.00, the insurance company retention, S is IDR200,000,000.00, the sensitivity minimum number of victims in one disaster event with 5 people. In conclusion, the reinsurance premium per year that must be paid by insurance companies to reinsurance companies will be increasing when the insurance company retention S is smaller, the maximum amount of risk covered by reinsurance L is greater, and the number of victims died u decreases.